(untitled) (Journal of Applied Learning and Teaching, 2025)
Background: This paper describes the protocol for a scoping review to map understandings of inclusion in Higher Education Institutions (HEIs) in the Republic of Ireland. To-date, there have been no scoping reviews published of the most current literature on inclusion in Irish HEIs. Method: Scoping reviews can inform decision-making and research as they involve rigorous identification and analysis of literature on a chosen subject. This search protocol will use the Arksey and O’Malley (2005) scoping review model to investigate empirical research and other relevant research, including grey literature, on inclusive practice in Irish HEIs from the years 1996 to 2023. The PRISMA extension for scoping reviews (PRISMA-ScR) will steer the scoping review itself. The following databases will be searched: ERIC, Scopus, Web of Science (Social Sciences Citation Index), and ASSIA; Google Scholar will be the final search tool. Thematic analysis will be used for appraisal and analysis of the data to assess inclusion in Irish HEIs. Results: This review is part of a wider study into inclusive practice in Irish Higher Education. It is envisaged that the scoping review that will follow this protocol will be published by Autumn 2025. Conclusion: This paper outlines the methodology for a comprehensive investigation into current understandings of inclusion in Irish HEIs. By systematically searching and analyzing relevant literature from 1996 to 2023, this review will identify key themes, gaps, and emerging trends in the field. The findings will help inform future research, policy development, and institutional strategies to enhance inclusion in Irish universities.